A method for preparing iron-tungsten loaded graphite felt for vanadium battery
By loading iron and tungsten on the graphite felt of the all-vanadium liquid flow battery electrode, and using hydrothermal treatment and high-temperature treatment, the problems of insufficient conductivity, poor catalytic activity and insufficient stability of the electrode are solved, and the efficiency and service life of the battery are improved.
Patent Information
- Application Number
- CN202411760749.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The electrodes of all vanadium flow battery have problems such as insufficient conductivity, poor catalytic activity and insufficient stability, which affect the efficiency and service life of the battery.
A preparation method for iron-tungsten-loaded graphite felt for vanadium batteries is adopted. By dissolving tungsten compounds, ferrous salts and surfactants in water, an electrodeposition solution is formed, and electrochemical deposition is performed after impregnation of the graphite felt, and then hydrothermal treatment is performed in an aqueous solution containing benzene peroxide and phenylenediamine substances, and finally nitrogen atmosphere is treated at high temperature to form iron-tungsten-loaded graphite felt for vanadium batteries.
By loading iron and tungsten on the graphite felt, the catalytic active sites and conductivity are improved, thereby improving the voltage efficiency and energy efficiency of the battery, improving the stability of the graphite felt, and extending the service life of the battery.
Smart Images

Figure CN119230853B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of all-vanadium liquid flow battery electrodes, and in particular to a method for preparing iron-tungsten loaded graphite felt for vanadium batteries. Background Art
[0002] All-vanadium flow batteries (vanadium batteries) achieve the conversion of electrical energy into chemical energy through the redox reaction of vanadium ions of different valence states in the positive and negative electrolytes. Electrodes are the core components of all-vanadium flow batteries, providing a place for redox reactions for the positive and negative energy storage active substances (vanadium ions of different valence states).
[0003] The requirements for electrodes of all-vanadium liquid flow batteries are: (1) high catalytic activity to reduce the internal resistance and activation polarization of the battery and improve the energy efficiency and voltage efficiency of the battery; (2) high conductivity to accelerate the transmission rate of electrons in the redox reaction and improve the energy efficiency and voltage efficiency of the battery; (3) excellent physical and chemical stability to ensure the long-term stable operation of the battery; (4) low price to facilitate large-scale commercial promotion.
[0004] At present, the modified electrodes of all-vanadium liquid flow batteries still have problems such as poor catalytic activity, poor conductivity and instability, which directly affect the efficiency and service life of all-vanadium liquid flow batteries, and thus cause an increase in construction costs, use costs and maintenance costs. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing iron-tungsten loaded graphite felt for vanadium batteries, so as to solve the problems of insufficient conductivity, poor catalytic activity and insufficient stability of all-vanadium liquid flow battery electrodes and improve the efficiency and service life of the battery.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing iron-tungsten loaded graphite felt for vanadium batteries comprises the following steps:
[0008] S1: dissolving tungstate compounds, ferrous salts and surfactants in water to obtain an electrodeposition solution;
[0009] S2: First, immerse the graphite felt in the electrodeposition solution, let it stand in vacuum for a period of time, take it out and use it as the working electrode in the electrochemical three-electrode system. The electrodeposition solution is the electrolyte, and electrochemical deposition is carried out by cyclic voltammetry. After completion, it is cleaned and dried to obtain the metal-loaded graphite felt;
[0010] S3: immersing the metal-loaded graphite felt in an aqueous solution containing benzene peroxide and phenylenediamine substances, hydrothermally treating, washing and drying, and obtaining a precursor graphite felt;
[0011] S4: subjecting the precursor graphite felt to high temperature treatment to obtain iron-tungsten loaded graphite felt for vanadium battery.
[0012] Preferably, the tungstate compound in step S1 is one of tungstic acid, sodium tungstate, potassium tungstate and ammonium tungstate, and the concentration of the tungstate compound in the electrodeposition solution is 0.05-0.2 mol / L.
[0013] Preferably, the ferrous salt in step S1 is one of ferrous sulfate, ferrous nitrate and ferrous acetate, and the concentration of the ferrous salt in the electrodeposition solution is 0.01-0.1 mol / L.
[0014] Preferably, the surfactant in step S1 is one of sodium dodecyl sulfate, sodium fatty acid methyl ester sulfonate, and sodium secondary alkyl sulfonate, and the concentration of the surfactant in the electrodeposition solution is 5-10 g / L.
[0015] Preferably, the vacuum degree of the vacuum standing in step S2 is 1-50 Pa, and the time is 1-3 hours.
[0016] Preferably, the scanning range of the cyclic voltammetry in step S2 is -1.2 to -0.3 V, the speed is 0.01 to 0.05 V / s, and the time is 0.5 to 2 h.
[0017] Preferably, the drying in step S2 is one of freeze drying and supercritical drying.
[0018] Preferably, the benzene peroxide in step S3 is one of benzoyl peroxide, 3-chloroperbenzoic acid, and tert-butyl perbenzoate, and the concentration of the benzene peroxide in the aqueous solution containing the benzene peroxide and phenylenediamine substances is 0.01-0.05 mol / L.
[0019] Preferably, the phenylenediamine substance in step S3 is one of o-phenylenediamine, p-phenylenediamine, m-phenylenediamine, 1,5-naphthalenediamine, naphthalene-1,4-diamine, and naphthalene-2,6-diamine; and the concentration of the phenylenediamine substance in the aqueous solution containing benzene peroxide and phenylenediamine substances is 0.05~0.3mol / L.
[0020] Preferably, the temperature of the hydrothermal treatment in step S3 is 150-250° C., and the time is 5-10 hours.
[0021] Preferably, in step S4, the high temperature treatment temperature is 600-800° C., the holding time is 2-4 hours, and the atmosphere is nitrogen.
[0022] Beneficial effects of the present invention:
[0023] 1. By loading iron and tungsten on graphite felt, the catalytic active sites and conductivity of graphite felt can be effectively improved, thereby improving the voltage efficiency and energy efficiency of the battery;
[0024] 2. The benzene peroxide in the present invention can not only partially oxidize tungsten, but also connect with the graphite carbon ring on the graphite felt fiber through π-π interaction. At the same time, the generated carboxylic acid further forms a condensate with the phenylenediamine substance under hydrothermal high temperature and high pressure conditions, firmly connecting iron and tungsten with the graphite felt, further improving the catalytic activity and stability of the graphite felt fiber;
[0025] 3. After tungsten is oxidized by benzene peroxide, the tungstic acid substances formed react hydrothermally in the presence of phenylenediamine and organic carboxylic acid to form tungsten oxide nanorods, which effectively improve the catalytic activity of graphite felt. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A schematic diagram of a method for preparing iron-tungsten loaded graphite felt for vanadium batteries according to the present invention;
[0027] Figure 2 SEM image of iron-tungsten loaded graphite felt for vanadium battery prepared in Example 1;
[0028] Figure 3 Cyclic voltammograms of the graphite felt obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0030] like Figure 1 As shown, a method for preparing iron-tungsten loaded graphite felt for vanadium battery comprises the following steps:
[0031] S1: Dissolve tungstic acid compounds, ferrous salts, and surfactants in water to obtain an electrodeposition solution; the tungstic acid compound is one of tungstic acid, sodium tungstate, potassium tungstate, and ammonium tungstate, and the concentration of the tungstic acid compound in the electrodeposition solution is 0.05~0.2mol / L. The ferrous salt is one of ferrous sulfate, ferrous nitrate, and ferrous acetate, and the concentration of the ferrous salt in the electrodeposition solution is 0.01~0.1mol / L. The surfactant is one of sodium dodecyl sulfate, sodium fatty acid methyl ester sulfonate, and sodium secondary alkyl sulfonate, and the concentration of the surfactant in the electrodeposition solution is 5~10g / L.
[0032] S2: First immerse the graphite felt in the electrodeposition solution, and let it stand for 1~3h with a vacuum degree of 1~50Pa. Then take it out as the working electrode in the electrochemical three-electrode system. The electrodeposition solution is the electrolyte. Cyclic voltammetry is used for electrochemical deposition. After completion, it is cleaned and dried to obtain metal-loaded graphite felt. The scanning range of the cyclic voltammetry is -1.2~-0.3V, the speed is 0.01~0.05V / s, and the time is 0.5~2h. The drying method is one of freeze drying and supercritical drying.
[0033] S3: The metal-loaded graphite felt is immersed in an aqueous solution containing benzene peroxide and phenylenediamines, subjected to hydrothermal treatment at 150-250°C for 5-10 hours, washed and dried to obtain a precursor graphite felt; the benzene peroxide is one of benzoyl peroxide, 3-chloroperbenzoic acid, and tert-butyl perbenzoate, and the concentration of the benzene peroxide in the aqueous solution containing benzene peroxide and phenylenediamines is 0.01-0.05 mol / L; the phenylenediamine is one of o-phenylenediamine, p-phenylenediamine, m-phenylenediamine, 1,5-naphthalenediamine, naphthalene-1,4-diamine, and naphthalene-2,6-diamine; the concentration of the phenylenediamine in the aqueous solution containing benzene peroxide and phenylenediamines is 0.05-0.3 mol / L.
[0034] S4: The precursor graphite felt is treated at a high temperature of 600-800°C in a nitrogen atmosphere for 2-4 hours to obtain iron-tungsten loaded graphite felt for vanadium battery.
[0035] Example 1: This example adopts the following scheme to prepare iron-tungsten loaded graphite felt for vanadium battery
[0036] Step S1: dissolving tungstic acid, ferrous sulfate and sodium dodecyl sulfate in water to obtain an electrodeposition solution, wherein the concentration of tungstic acid compounds is 0.05 mol / L, the concentration of ferrous salt is 0.01 mol / L, and the concentration of surfactant is 5 g / L;
[0037] Step S2: first immerse the graphite felt in the electrodeposition solution, and let it stand for 1 hour with a vacuum degree of 1Pa, and take it out as the working electrode in the electrochemical three-electrode system, set the scanning range to -1.2~-0.3V, the speed to 0.01V / s, and the time to 0.5h. The electrodeposition solution is the electrolyte, and the electrochemical deposition is carried out by cyclic voltammetry. After completion, it is washed and freeze-dried to obtain the metal-loaded graphite felt;
[0038] Step S3: immersing the metal-loaded graphite felt in an aqueous solution containing benzoyl peroxide and o-phenylenediamine, wherein the concentration of benzene peroxide is 0.01 mol / L, and the concentration of phenylenediamine is 0.05 mol / L, hydrothermally treating at 150° C. for 10 h, washing and drying, to obtain a precursor graphite felt;
[0039] Step S4: treating the precursor graphite felt at 600° C. for 4 h in a nitrogen atmosphere to obtain iron-tungsten loaded graphite felt for vanadium battery.
[0040] Figure 2 (A) is the SEM image of the initial graphite felt. It can be seen that the fiber surface is smooth and has no particle loading. Figure 2 (B) is a SEM image of iron-tungsten loaded graphite felt for vanadium batteries. It can be seen that there are particles loaded on the fiber surface. Figure 2 (C) is an enlarged SEM image of the material loaded on the fiber surface, and it can be seen that there are particles and rod-shaped objects, which indicates that the method of the present application can realize the loading of iron and tungsten on the graphite felt.
[0041] Example 2: This example adopts the following scheme to prepare iron-tungsten loaded graphite felt for vanadium battery
[0042] Step S1: dissolving sodium tungstate, ferrous nitrate and sodium fatty acid methyl ester sulfonate in water to obtain an electrodeposition solution, wherein the concentration of tungstate compound is 0.2 mol / L, the concentration of ferrous salt is 0.1 mol / L, and the concentration of surfactant is 10 g / L;
[0043] Step S2: first immerse the graphite felt in the electrodeposition solution, and place it at a vacuum of 50 Pa for 3 hours, and then take it out as the working electrode in the electrochemical three-electrode system, set the scanning range to -1.2~-0.3V, the speed to 0.05V / s, and the time to 2 hours, and use the electrodeposition solution as the electrolyte to perform electrochemical deposition by cyclic voltammetry, and then wash and supercritically dry after completion to obtain metal-loaded graphite felt;
[0044] Step S3: immersing the metal-loaded graphite felt in an aqueous solution containing 3-chloroperoxybenzoic acid and p-phenylenediamine, wherein the concentration of benzene peroxide is 0.05 mol / L and the concentration of phenylenediamine is 0.3 mol / L, hydrothermally treating at 250° C. for 5 h, washing and drying to obtain a precursor graphite felt;
[0045] Step S4: treating the precursor graphite felt at 800° C. for 2 h in a nitrogen atmosphere to obtain iron-tungsten loaded graphite felt for vanadium battery.
[0046] Example 3: This example adopts the following scheme to prepare iron-tungsten loaded graphite felt for vanadium battery
[0047] Step S1: dissolving potassium tungstate, ferrous acetate and sodium secondary alkyl sulfonate in water to obtain an electrodeposition solution, wherein the concentration of tungstate compounds is 0.1 mol / L, the concentration of ferrous salt is 0.05 mol / L, and the concentration of surfactant is 8 g / L;
[0048] Step S2: first immerse the graphite felt in the electrodeposition solution, set the vacuum degree to 30Pa and let it stand for 2 hours, take it out as the working electrode in the electrochemical three-electrode system, set the scanning range to -1.2~-0.3V, the speed to 0.03V / s, the time to 1h, the electrodeposition solution to be the electrolyte, and use cyclic voltammetry to perform electrochemical deposition. After completion, wash and freeze-dry to obtain the metal-loaded graphite felt;
[0049] Step S3: immersing the metal-loaded graphite felt in an aqueous solution containing tert-butyl perbenzoate and m-phenylenediamine, wherein the concentration of benzene peroxide is 0.03 mol / L, and the concentration of phenylenediamine is 0.1 mol / L, hydrothermally treating at 200° C. for 7 h, washing and drying, to obtain a precursor graphite felt;
[0050] Step S4: treating the precursor graphite felt at 700° C. for 3 h in a nitrogen atmosphere to obtain iron-tungsten loaded graphite felt for vanadium battery.
[0051] Example 4: This example adopts the following scheme to prepare iron-tungsten loaded graphite felt for vanadium battery
[0052] Step S1: dissolving ammonium tungstate, ferrous sulfate and sodium dodecyl sulfate in water to obtain an electrodeposition solution, wherein the concentration of tungstate compounds is 0.15 mol / L, the concentration of ferrous salt is 0.04 mol / L, and the concentration of surfactant is 7 g / L;
[0053] Step S2: first immerse the graphite felt in the electrodeposition solution, set the vacuum degree to 20Pa and let it stand for 2 hours, take it out as the working electrode in the electrochemical three-electrode system, set the scanning range to -1.2~-0.3V, the speed to 0.02V / s, the time to 2 hours, the electrodeposition solution to be the electrolyte, and use cyclic voltammetry to perform electrochemical deposition. After completion, wash and freeze-dry to obtain the metal-loaded graphite felt;
[0054] Step S3: immersing the metal-loaded graphite felt in an aqueous solution containing benzoyl peroxide and 1,5-naphthalenediamine, wherein the concentration of benzene peroxide is 0.02 mol / L, and the concentration of phenylenediamine is 0.2 mol / L, hydrothermally treating at 180° C. for 8 h, washing and drying, to obtain a precursor graphite felt;
[0055] Step S4: treating the precursor graphite felt at 800° C. for 2 h in a nitrogen atmosphere to obtain iron-tungsten loaded graphite felt for vanadium battery.
[0056] Example 5: This example adopts the following scheme to prepare iron-tungsten loaded graphite felt for vanadium battery
[0057] Step S1: dissolving sodium tungstate, ferrous sulfate and sodium dodecyl sulfate in water to obtain an electrodeposition solution, wherein the concentration of tungstate compounds is 0.2 mol / L, the concentration of ferrous salt is 0.08 mol / L, and the concentration of surfactant is 6 g / L;
[0058] Step S2: first immerse the graphite felt in the electrodeposition solution, and place it at a vacuum of 10 Pa for 2 hours, and then take it out as the working electrode in the electrochemical three-electrode system, set the scanning range to -1.2~-0.3V, the speed to 0.04V / s, and the time to 1.5h. The electrodeposition solution is the electrolyte, and the electrochemical deposition is performed by cyclic voltammetry. After completion, it is washed and freeze-dried to obtain the metal-loaded graphite felt;
[0059] Step S3: immersing the metal-loaded graphite felt in an aqueous solution containing benzoyl peroxide and naphthalene-1,4-diamine, wherein the concentration of benzene peroxide is 0.04 mol / L, and the concentration of phenylenediamine is 0.15 mol / L, hydrothermally treating at 220° C. for 6 h, washing and drying, to obtain a precursor graphite felt;
[0060] Step S4: treating the precursor graphite felt at 800° C. for 2 h in a nitrogen atmosphere to obtain iron-tungsten loaded graphite felt for vanadium battery.
[0061] Example 6: This example adopts the following scheme to prepare iron-tungsten loaded graphite felt for vanadium battery
[0062] Step S1: dissolving ammonium tungstate, ferrous acetate and sodium fatty acid methyl ester sulfonate in water to obtain an electrodeposition solution, wherein the concentration of tungstate compound is 0.05 mol / L, the concentration of ferrous salt is 0.01 mol / L, and the concentration of surfactant is 5 g / L;
[0063] Step S2: first immerse the graphite felt in the electrodeposition solution, set the vacuum degree to 30Pa and let it stand for 3 hours, take it out as the working electrode in the electrochemical three-electrode system, set the scanning range to -1.2~-0.3V, the speed to 0.01V / s, the time to 2h, the electrodeposition solution to be the electrolyte, and use cyclic voltammetry to perform electrochemical deposition. After completion, wash and freeze-dry to obtain the metal-loaded graphite felt;
[0064] Step S3: immersing the metal-loaded graphite felt in an aqueous solution containing 3-chloroperbenzoic acid and naphthalene-2,6-diamine, wherein the concentration of benzene peroxide is 0.02 mol / L, and the concentration of phenylenediamine is 0.1 mol / L, hydrothermally treating at 200° C. for 8 h, washing and drying, to obtain a precursor graphite felt;
[0065] Step S4: treating the precursor graphite felt at 700° C. for 3 h in a nitrogen atmosphere to obtain iron-tungsten loaded graphite felt for vanadium battery.
[0066] Comparative Example 1: Untreated graphite felt.
[0067] Comparative Example 2: This comparative example differs from Example 1 in that steps S1 and S2 are not performed.
[0068] Comparative Example 3: This comparative example differs from Example 1 in that step S3 is not performed.
[0069] Figure 3 The cyclic voltammograms of the graphite felts obtained in Example 1 and Comparative Example 1 show that both graphite felts have two obvious current peaks, among which the graphite felt in Example 1 has the largest response current density, and the current density ratio of the oxidation peak to the reduction peak (I pa / I pc ) is closer to 1, indicating that the symmetry of the oxidation and reduction current density of the graphite felt electrode prepared in Example 1 is better, and the kinetic reversibility is improved. In addition, the starting potential and the redox peak potential difference ΔE of the oxidation process of the graphite felt electrode in Example 1 are smaller, indicating higher electrochemical activity.
[0070] Vanadium battery performance test: The graphite felts obtained in Examples 1-6 and Comparative Examples 1-3 were assembled into a vanadium battery stack, and a charge and discharge cycle test was performed under the same working conditions, and the battery efficiency and were recorded, as shown in Table 1.
[0071] Table 1 Summary of vanadium battery stack test results
[0072]
[0073] The battery test results are shown in Table 1. It can be seen that compared with Comparative Examples 1 and 3, Examples 1-6 have higher energy efficiency and voltage efficiency. This is mainly because the iron and tungsten loaded on the graphite felt can effectively improve the catalytic active sites and conductivity of the graphite felt, thereby improving the voltage efficiency and energy efficiency of the battery. However, the coulombic efficiency of Comparative Example 3 is reduced, mainly because the simply electrodeposited iron and tungsten have poor bonding with the graphite felt fibers, are easy to fall off, consume electrical energy, and cause a decrease in coulombic efficiency. Compared with Comparative Examples 1 and 2, Examples 1-6 have higher energy efficiency and voltage efficiency, mainly because the benzene peroxide can not only partially oxidize tungsten, but also connect with the graphite carbon rings on the graphite felt fibers through π-π forces. At the same time, the generated carboxylic acid further forms a condensation product with diphenylamine substances under hydrothermal high temperature and high pressure conditions, firmly connecting iron and tungsten to the graphite felt, further improving the catalytic activity and stability of the graphite felt fibers. In addition, after tungsten is oxidized by diphenylamine, the formed tungsten acid substances undergo a hydrothermal reaction in the presence of diphenylamine and organic carboxylic acids to form tungsten oxide nanorods, effectively improving the catalytic activity of the graphite felt.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing iron-tungsten loaded graphite felt for vanadium batteries, characterized in that: The steps include: S1: dissolving tungstate compounds, ferrous salts and surfactants in water to obtain an electrodeposition solution; S2: First, immerse the graphite felt in the electrodeposition solution, let it stand in vacuum for a period of time, take it out and use it as the working electrode in the electrochemical three-electrode system. The electrodeposition solution is the electrolyte, and electrochemical deposition is carried out by cyclic voltammetry. After completion, it is cleaned and dried to obtain iron-tungsten loaded graphite felt; S3: Immerse the iron-tungsten loaded graphite felt in an aqueous solution containing benzene peroxide and phenylenediamine substances, perform hydrothermal treatment, clean and dry, and perform high-temperature treatment to obtain iron-tungsten loaded graphite felt for vanadium batteries; the hydrothermal treatment temperature is 150~250℃, and the time is 5~10h; the high-temperature treatment temperature is 600~800℃, the insulation time is 2~4h, and the atmosphere is nitrogen.
2. The method for preparing iron-tungsten loaded graphite felt for vanadium battery according to claim 1, characterized in that: In step S1, the tungstate compound is one of tungstic acid, sodium tungstate, potassium tungstate and ammonium tungstate, and the concentration of the tungstate compound in the electrodeposition solution is 0.05-0.2 mol / L.
3. The method for preparing iron-tungsten loaded graphite felt for vanadium battery according to claim 1, characterized in that: In step S1, the ferrous salt is one of ferrous sulfate, ferrous nitrate and ferrous acetate, and the concentration of the ferrous salt in the electrodeposition solution is 0.01-0.1 mol / L.
4. The method for preparing iron-tungsten loaded graphite felt for vanadium battery according to claim 1, characterized in that: In step S1, the surfactant is one of sodium dodecyl sulfate, sodium fatty acid methyl ester sulfonate, and sodium secondary alkyl sulfonate, and the concentration of the surfactant in the electrodeposition solution is 5-10 g / L.
5. The method for preparing iron-tungsten loaded graphite felt for vanadium battery according to claim 1, characterized in that: The vacuum degree of the vacuum standing in step S2 is 1-50 Pa, and the time is 1-3 hours.
6. The method for preparing iron-tungsten loaded graphite felt for vanadium battery according to claim 1, characterized in that: In step S2, the scanning range of the cyclic voltammetry is -1.2 to -0.3 V, the speed is 0.01 to 0.05 V / s, and the time is 0.5 to 2 h; and the drying is one of freeze drying and supercritical drying.
7. The method for preparing iron-tungsten loaded graphite felt for vanadium battery according to claim 1, characterized in that: In step S3, the benzene peroxide is one of benzoyl peroxide, 3-chloroperbenzoic acid, and tert-butyl perbenzoate, and the concentration of the benzene peroxide in the aqueous solution containing the benzene peroxide and the phenylenediamine substances is 0.01-0.05 mol / L.
8. The method for preparing iron-tungsten loaded graphite felt for vanadium battery according to claim 1, characterized in that: In step S3, the phenylenediamine substance is one of o-phenylenediamine, p-phenylenediamine, m-phenylenediamine, 1,5-naphthalenediamine, naphthalene-1,4-diamine, and naphthalene-2,6-diamine; and the concentration of the phenylenediamine substance in the aqueous solution containing benzene peroxide and phenylenediamine substances is 0.05-0.3 mol / L.
Citation Information
Patent Citations
Method for chemically plating Ni-W-P on carbon felt electrode material of modified redox flow battery
CN103985883A
Negative electrode for all-vanadium redox flow battery, preparing method of negative electrode, and vanadium redox flow battery
CN108461758A